Jung and 'Africans': a critical and contemporary review of some of the issues*. Issue 2 (4th May 2018) - Samuels, Andrew
ABSTRACT: This paper is written in the context of a debate within the Jungian clinical and academic communities on whether or not some kind of public statement is required concerning Jung's writings about 'Africans', persons of colour and indigenous people. The author eschews argument in favour of such a public statement, opting instead for a 'forensic' discussion of the reasons why it is not a good plan to issue such a statement. By so doing, he creates a level playing field in which the 'pros' and 'cons' of a public statement may attract equal attention.